(untitled) (Journal of the College of Basic Education, 2023)
A study aimed at analyzing the metadata elements (160180818/2) of a sample of websitesIraqi universities; Using the analysis program, (6) sites were selected:Baghdad, Basra, Kufa, Karbala; technological scourge; The analysis process revealed a vulnerability usingmetadata in those sites compared to international standards; And its lack of accurate expression of the objective contentFor the selected sites, the most prominent failures were identified.The study presented a number of recommendations, including the adoption of the Dublin Core Standard (which is generally characterized by simplicity).and lack of complexity) in the use of metadata when building its paragraphs; This is due to its ability to quickly searchWhich allows the beneficiary to make various search inquiries and the necessary modifications to them and benefit from themwhen designing websites online.